Indonesian Horizons in Islamic Finance: Navigating Risk, Innovation, and Social Impact - Ibrahim, Azharsyah (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This edition of "Share: Journal of Islamic Economics and Finance" presents a diverse range of insightful research and findings exploring various aspects of Islamic economics and finance. The studies cover topics such as the innovative Micro Waqf Bank model in Aceh, determinants of risk in Indonesian Islamic banking, Ibn Khaldun's nuanced theory of economic development, the potential of Cash Waqf Linked Deposit (CWLD) in revitalizing Islamic banking, financial performance evaluation of mining companies listed on the Jakarta Islamic Index, redefining Customer Relationship Management (CRM) for the digital age, the influence of Islamic marketing strategies on pre-loved clothing purchases, the nexus between Sharia governance and financial performance in Indonesian Islamic banks, mitigation strategies for Islamic financing risk, the impact of temporary shirkah funds on SME financing, a gravity model analysis of Indonesia's trade role within OIC economies, protection of Hajj and Umrah pilgrims from fraud, the role of fintech lending in expanding Sharia financial inclusion and human development, the mediating role of perceived usefulness in Sharia fintech adoption among Gen Z, the SDG-Islamic banking nexus in major OIC economies, the impact of macroeconomics on Islamic banking and MSME futures during the COVID-19 crisis, and the transition to Sharia-compliant finance in Aceh amidst miscommunication, misperceptions, and resistance. These studies employ various methodologies, including quantitative analysis, qualitative approaches, and mixed methods, to investigate the challenges, opportunities, and innovations within the field of Islamic economics and finance. The findings contribute to a deeper understanding of Islamic economic thought, sustainable development, risk management, financial inclusion, customer relationship management, and the role of Islamic finance in promoting economic growth and social welfare. The studies also offer practical implications and recommendations for policymakers, regulators, Islamic financial institutions, and researchers, paving the way for a more dynamic, inclusive, and sustainable Islamic financial landscape.